FACTORS AFFECTING ONLINE HOTEL BOOKING INTENTION: A STUDY ON UUM STUDENTS (Journal of Technology and Operations Management, 2022)
With the high-speed development of the Internet and artificial intelligence, the hotel booking method was also undergoing innovative changes. Compared with traditional information dissemination media, the Internet has a stronger dissemination ability, wider scope and larger audience. Online reviews about one's experience in using hotel service could be simply disseminated using the Internet platform, which consequently affects the hotel booking intention of future customers. In this regard, it is vital to understand the impact of online reviews on hotel booking intentions in order to develop strategies that will sustain the hotel industry. This study examined the impact of online review in four dimensions which are usefulness, valence, volume and trust towards online hotel booking intention. Besides, the study also investigated the role of self-efficacy towards online hotel booking intention to capture the user's technological capacity dimension. Data were collected using survey questionnaires from 255 UUM undergraduate students. The analysis was performed with the aid of SPSS statistical analysis software. The results suggest that only two dimensions in the online review have significant impact toward online hotel booking intention, namely volume and trust. Moreover, the role of self-efficacy was not observed. Studying online reviews and consumer behavior is beneficial for hotel managers to have a more comprehensive grasp of the factors that affect customers' intention to book hotels online. Implications of this study are further discussed.